2009
DOI: 10.1200/jco.2009.27.15_suppl.e15017
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation profile in colorectal cancer patients in Brazil: A cohort of 989 individuals

Abstract: e15017 Background: KRAS mutation is common event in colorectal cancer occurring in around 40% of the patients. It is well- known that patients harboring the KRAS mutation do not derive benefit from cetuximab. However data available KRAS mutation profile is limited to Caucasian and Asian individuals and there is a lack of data in the population from Latin America. Brazilian population has a heterogeneous genetic background and this may have pharmacogenetic implications (Suarez-Kurtz, 2006). Methods: Between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Mutant K-RAS was found in 39.5% of rectum carcinomas, in which a 12 Val mutation was observed (37.5%). Similarly to previous findings, a K-RAS mutation was observed in proximal tumors (p=0.023) and in tumors with distant metastasis (p=0.020) (15,16). Conversely, one study did not find any statistically significant correlation between proximal tumor location, higher tumor grade, and absence of peritumoral lymphocytic inflammation and mutant K-RAS (17).…”
Section: Discussionsupporting
confidence: 87%
“…Mutant K-RAS was found in 39.5% of rectum carcinomas, in which a 12 Val mutation was observed (37.5%). Similarly to previous findings, a K-RAS mutation was observed in proximal tumors (p=0.023) and in tumors with distant metastasis (p=0.020) (15,16). Conversely, one study did not find any statistically significant correlation between proximal tumor location, higher tumor grade, and absence of peritumoral lymphocytic inflammation and mutant K-RAS (17).…”
Section: Discussionsupporting
confidence: 87%
“…The findings of these investigations corroborate our study's outcome that approximately thirty-six percent of the patients have KRAS gene mutation. This prevalence rate was similar to data reported from the US (35.7% [104] and 31% [105]), China (32%) [106], Japan (33.5%) [107], Taiwan (33.5%) [37], Russia (35.9%) [108], France (33.8) [109], the United Kingdom (36.9%) [110], and Brazil (36%) [111], although KRAS prevalence was reported to slightly differ from some published data from Germany (41%) [112], Italy (62.2%, 43%, and 43%) [113][114][115], Turkey (44%) [116], Morocco (24%) [117], and Egypt (11% and18.4%) [118,119]. These latter differences could be associated with various factors such as race, lifestyle, period, and means of sample collection and geographical locations.…”
Section: Discussionsupporting
confidence: 89%
“… 93 Consistent results were reported in a large-scale study in Brazil, with KRAS mutations in codons 12 and 13 found in 87% and 13% of patients, respectively. 68 However, a study on the Greek population reported a lower frequency of KRAS mutations in codon 12, at 29.3%. 94 Various genetic and environmental factors contribute to the frequency and distribution of KRAS mutations, leading to variations across different ethnic populations.…”
Section: Discussionmentioning
confidence: 98%
“…Although some studies suggest a higher likelihood of mutant KRAS in women, 66 , 67 others indicate the opposite trend. 43 , 68 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation